2016
DOI: 10.1080/09638288.2016.1247470
|View full text |Cite
|
Sign up to set email alerts
|

Getting help quickly: older people and community worker perspectives of contingency planning for falls management

Abstract: Objective Despite consistent evidence for the positive impact of contingency planning for falls in older people, implementation of plans often fail. This is likely due to lack of recognition and knowledge about perspectives of older people about contingency planning. The objective of this research was to explore the perspectives of older people living in the community about use of contingency planning for getting help quickly after a fall. Method A systematic literature search seeking qualitative research was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…However, the government usually formulates one size-fits-all plans. As this study shows, rural areas with various communities needed personalized help, driving citizen-centered organizations [25,26]. Furthermore, communities need different kinds of help from various organizations to solve problems.…”
Section: Discussionmentioning
confidence: 90%
“…However, the government usually formulates one size-fits-all plans. As this study shows, rural areas with various communities needed personalized help, driving citizen-centered organizations [25,26]. Furthermore, communities need different kinds of help from various organizations to solve problems.…”
Section: Discussionmentioning
confidence: 90%
“…Correspondingly, a study with both men and women reported how a male participant believed that his pride was a barrier for making contingency plans. The male participant did not like using assisting devices (such as his four‐wheeled walker), which he believed would stigmatize him as someone who needed help (Charlton et al, ). These findings therefore indicate that the need for assistive technology and aids could be even higher than shown in our study, but male persons might have refrained in expressing these needs after their fall experience.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated various aspects regarding older persons after a fall event showing that they fear the consequences of falling (Tischler & Hobson, ), that falls can result in a decline in health status, ability to undertake activities of living, lifestyle and quality of life (Roe et al, ), but also that some accept fear of falling as a part of life (Mahler & Sarvimaki, ) and that older people can be embarrassed about wearing visible falls detection technology (Charlton, Murray, & Kumar, ). Furthermore, it has been reported that older women make a range of postfall responses and decisions, including engaging in the extra work required to get back to normal, purposefully avoiding people, objects and places, being proactive and planning ahead and putting the fall out of mind (Bergeron, Friedman, Messias, Spencer, & Miller ).…”
Section: Introductionmentioning
confidence: 99%
“…This research about contingency planning addresses a largely neglected aspect of falls management [14] Best practice guidelines present information and evidence about strategies for falls prevention but options given to health professionals for getting help quickly after a fall are limited [2]. The findings of this meta-synthesis reveal that whilst family members and health professionals may have good intentions in recommending and implementing contingency plans for an older person to get help quickly in the event of a fall (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…If the system detects a fall, it will automatically activate to get assistance. Research has found that older participants were accepting of automated wearable fall detectors [13] but there were associated feelings of increased vulnerability and worry about impact on identity [14] invasion of privacy and concerns about cost, appearance and maintenance of the technology [7]. …”
Section: Introductionmentioning
confidence: 99%